OXA-28, an Extended-Spectrum Variant of OXA-10 β-Lactamase from Pseudomonas aeruginosa and Its Plasmid- and Integron-Located Gene - Poirel, Laurent (American Society for Microbiology, 2001)
Pseudomonas aeruginosa ED-1, isolated from a pulmonary brush of a patient hospitalized in a suburb of Paris, France, was resistant to ceftazidime and of intermediate susceptibility to ureidopenicillins and to cefotaxime. Cloning and expression of the β-lactamase gene content of this isolate in Escherichia coli DH10B identified a novel OXA-10 variant, OXA-28, with a pI value of 8.1 and a molecular mass of 29 kDa. It differed from OXA-10 by 10 amino acid changes and from OXA-13 and OXA-19 by 2 amino acid changes, including a glycine instead of tryptophan at position 164, which is likely involved in its resistance to ceftazidime. Like OXA-11, -14, -16, and -19 and as opposed to OXA-17, OXA-28 predominantly compromised ceftazidime and had only marginal effect on the MICs of aztreonam and cefotaxime in P. aeruginosa. Once expressed in E. coli, OXA-28 raised the MIC of ceftazidime to a much higher level than those of amoxicillin, cephalothin, and cefotaxime (128, 16, 8, and 4 μg/ml, respectively). OXA-28 β-lactamase had a broad spectrum of activity, including ceftazidime. Its activity was partially antagonized by clavulanic acid (50% inhibitory concentration, 10 μM) and NaCl addition. The oxa28 gene cassette was inserted in the variable region of a class 1 integron, In57, immediately downstream of an amino 6′-N-acetyltransferase gene cassette, aac(6′)Ib. The structures of the integrons carrying either oxa28, oxa13, or oxa19 gene cassettes were almost identical, suggesting that they may have derived from a common ancestor as a result of the common European origin of the P. aeruginosa isolates. In57 was located on a self-transferable plasmid of ca. 150 kb that was transferred from P. aeruginosa to P. aeruginosa.